PERANAN ETIKA DAN TANGGUNG JAWAB SOSIAL DALAM BISNIS INTERNASIONAL - Siti Nur Hazizah; Nuri Aslami (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
International business occurs one of them because of the inability of a country in meeting all the needs of its country, therefore came the idea of establishing cooperation between one country and another country. This research aims to find out the role of ethics and social responsibility in international business. This research uses a qualitative approach that describes and outlines the role of ethics and social responsibility in international business. The data collection technique used in this research is a literature study, where the study is conducted by collecting data related to research derived from books, scientific journals and other publications that deserve to be a source of research. The results of this study show that ethics and social business responsibility have the same role that aims to improve the company's image and develop the company. A business will not be able to develop without the role of consumers, because the main purpose of the company besides benefiting is to be able to attract consumer interest and gain the trust of consumers and business partners.